A POLICY EVALUATION OF THE SMART INDONESIAN PROGRAMME (PIP) IN ENCOURAGING THE IMPLEMENTATION OF 12-YEAR COMPULSORY EDUCATION IN SUKABUMI DISTRICT - Iwan, Iwan; Rachmawati, Ike; Nibi Saputra, Unin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aims to evaluate the Smart Indonesia Programme policy in encouraging the implementation of 12 years of compulsory education in the Sukabumi District. This study uses a descriptive qualitative method. Data collection techniques included interviews, observation, and document analysis. Data analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The results showed (1) the context aspect was by the criteria, due to the suitability of the background of program implementation, legal basis, and objectives of the PIP program. (2) the input aspect is by the criteria, the implementation and acceptance mechanism of the PIP program is under the applicable program Technical Guidelines, (3) the process aspect is by the criteria, the implementation of disbursement, distribution, utilization and supervision of the program has been carried out by applicable regulations, (4) the product aspect is not by the criteria, it can be seen from the increasing dropout rate, for this reason schools need to motivate students so that they can see the purpose of implementing compulsory 12-year education.